Onze vriend op de pauwentroon - Warnaar, Maaike (Amsterdam University Press, 2023)
Reading the news about Iran today one can hardly imagine that relations between the Netherlands and Iran were excellent until 1979. Mohammed-Reza Pahlavi, the last shah of Persia, was known in The Netherlands as a visionary and reformer. Persia was represented as a mythical land with an ancient civilization. The Dutch royal family enjoyed visiting the shah, and large and small Dutch companies were successful in Iran.